The ideal swimmer's body (2000)
Factors other than height and leanness can contribute to swimming success. This research at the U.S. Olympic Training Center in Colorado Springs has identified several of these factors: center of mass (COM), body density (DEN), physiology, anthropometry, hull length and shape, strength profile, leg power and feel for the water. Two other factors are also significant, especially for Masters swimmers: flexibility and percent body fat. Let's look at each of these.